"Fat-proof your child": Parenting advice and "child obesity". Issue 2 (2nd July 2016) - Quirke, Linda
ABSTRACT: How are fat children represented in media parenting advice? I examine how fat children and "childhood obesity" are depicted in popular media, using dominant cultural models of child fatness and the "obesity epidemic, " as presented in two flagship parenting magazines over the past three decades. Profiling the specific life experiences of individual children and their parents, parenting magazines offer "expert" advice and everyday tips for managing children's weight. I examine the advice dispensed by two parenting magazines: one from the United States ( Parents ) and one from Canada ( Today's Parent ). I perform a content analysis of 104 articles (52 from each publication) that appeared in print between 1983 and 2014. This longitudinal approach allows for analysis of both historical and current characterizations of fat children as a social problem. This analysis finds that parenting magazines present the "obesity epidemic" as fact, as they characterize fat as a serious health problem, offering ways to intervene and more recently, to prevent "child obesity." Articles consistently and fearfully detail numerous negative health consequences that may befall fat children. In recent years all children are cast as passive and at risk for becoming fat. Individual parents, generally mothers, are presented as singularly responsible for children's health, in contrast with earlier years, when children were seen as largely responsible for their own fatness. Fat is depicted as a medical problem to be solved through diligent, early intervention. Keeping children ignorant of the stigma associated with fatness is lauded. Ultimately, these media representations of "child obesity" endorse a gendered and classed, intensive model of parenting that assumes that parents should closely oversee and manage susceptible children.